Electrodeposition of ZnO Nanoprism-Zn substituted hydroxyapatite duplex layer coating for carbon fiber. Issue 11 (1st August 2019) - Pei, Lina; Zhang, Boxin; Luo, Hao; Wu, Xiaochen; Li, Gangquan; Sheng, Hongchao; Zhang, Leilei
Abstract: A ZnO nanoprism/Zn substituted hydroxyapatite duplex layer (ZnOnp-ZnHA) coating was prepared on carbon fibers (CF) by two-step electrodeposition method. The ZnOnp-ZnHA coating on CF was characterized by Scanning Electron Microscopy, Transmission Electron Microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, Energy dispersive spectrometer, Raman spectra and Thermogravimetric Analysis. The formation mechanism of the duplex layer coating was discussed. The in-vitro bioactivity of the duplex layer coating was investigated by simulated body fluid (SBF) immersion test. The ZnOnp interlayer showed nanoprism morphology with a length of 0.4–0.9 μm and a diameter of 117–220 nm. We found both the CF and the ZnOnp could serve as nucleation sites for ZnHA layer. The ZnHA outer layer showed ball-like morphology with a diameter of 0.6–1.7 μm. The duplex layer coating exhibited suitable in-vitro bioactivity using SBF immersion test method. The ZnOnp-ZnHA duplex layer coated CF may serve as a promising candidate for clinic applications.